Two sides of the coin: Amiodarone-induced lung toxicity – Case Report - Klaudiusz Garbacki; Katarzyna Jóźwik; Klaudia Kleczaj; Klaudia Ciupak; Piotr Kulig; Ewa Kurys-Denis; Luiza Grzycka-Kowalczyk; Anna Grzywa-Celińska (Journal of Pre-Clinical and Clinical Research, 2022)
Introduction . Amiodarone is often used in the treatment of arrhythmias. Despite its undoubtedly excellent antiarrhythmic effect, its use can also causa serious adverse effects. This case report presents a patient who, after several months of treatment with amiodarone, developed severe pulmonary complications and transient liver injury. Despite discontinuation of the drug and implementation of optimal treatment aimed at harm reduction, a full resolution of the pulmonary lesions was not achieved. Objective . The aim of the report is to draw attention to the risks to the respiratory system associated with the use of amiodarone. It is worth noting that some symptoms of post-amiodarone lung damage may resemble the exacerbation of heart failure, which contributes to the delay of a correct diagnosis and prolongs the time to the start treatment.